Simulation of Evacuation Dynamics in Fire by Cellular Automata - YAMAMOTO, Kazuhiro; KOKUBO, Satoshi; YAMASHITA, Hiroshi (Nihon Kikai Gakkai rombunshuu. B hen, 2008)
Since Cellular Automata (CA) was proposed by von Neumann in the late 1940s, CA have been applied in a variety of scientific researches on complex system, including traffic models and biological fields. It is an idealization of a physical system in which space and time are all discrete. In this study, we have simulated evacuation dynamics in fire by Real-coded Cellular Automata (RCA) proposed as a new approach for pedestrian flow. To consider the flame spread in discrete time and space in calculation, a percolation model is used. We change initial number of people, evacuee velocity, exit width, and flame spread rate. We discuss the total evacuation time and number of fatalities involved in fire.